2022
DOI: 10.1038/s41598-022-22117-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of visual crossmodal reorganization positively relates to speech outcomes in cochlear implant users

Abstract: Deaf individuals who use a cochlear implant (CI) have remarkably different outcomes for auditory speech communication ability. One factor assumed to affect CI outcomes is visual crossmodal plasticity in auditory cortex, where deprived auditory regions begin to support non-auditory functions such as vision. Previous research has viewed crossmodal plasticity as harmful for speech outcomes for CI users if it interferes with sound processing, while others have demonstrated that plasticity related to visual languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Recent investigators ( Chen et al, 2017 ; Fullerton et al, 2023 ; Paul et al, 2022 ) have questioned the classical view ( Lee et al, 2001 ) that cross-modal plasticity negatively affects speech performances of participants with CI. Cortical reorganization following CI may not always prevent the auditory cortex from responding to auditory stimuli ( Land et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigators ( Chen et al, 2017 ; Fullerton et al, 2023 ; Paul et al, 2022 ) have questioned the classical view ( Lee et al, 2001 ) that cross-modal plasticity negatively affects speech performances of participants with CI. Cortical reorganization following CI may not always prevent the auditory cortex from responding to auditory stimuli ( Land et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with more recent studies supporting a beneficial role of visual language input on auditory outcomes in CI users. A recent study by Paul et al (2022) used electroencephalography to measure crossmodal visual responses in auditory cortex and related these to speech-in-noise perceptual abilities. Those authors found that CI users with higher speech perception scores demonstrated stronger responses in auditory cortex to visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of AV speech recognition in clinical populations of patients with moderate-to-profound HL have been done in established postlingually deaf adult CI users with substantial experience using their devices (Rabinowitz et al 1992;Kaiser et al 2003;Hay-McCutcheon et al 2005;Rouger et al 2007;Desai et al 2008;Strelnikov et al 2009;Altieri et al 2011;Stevenson et al 2017;Schreitmüller et al 2018). In those studies, investigators have found that experienced CI users (ECIs) demonstrated greater benefits from visual cues than normal-hearing peers during AV speech recognition (Desai et al 2008;Rouger et al 2008;Leybaert & LaSasso 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to previous concerns about potential interference between visual sign language and auditory processing via CI, emerging studies have highlighted a different perspective. This updated discourse centers on the idea that signed language, as a visual modality, may not necessarily hinder the development of crucial auditory skills in CI users ( Cardin et al, 2016 ; Corina et al, 2017 ; Paul et al, 2022 ; see Land et al, 2016 , for animals). Instead, as speech inherently is multimodal (i.e., auditory speech signal is accompanied by visual of mouth movements), incorporating signed language alongside CI use may serve as a vital bridge between different sensory experiences, enhancing comprehension and communication.…”
Section: Introductionmentioning
confidence: 99%